Improving the performance of high occupancy vehicle infrastructure to alleviate city congestion - Nkadile, Laone (Central University of Technology, 2022)
The rate of rural-urban migration has increased demand on the infrastructural facilities in cities and towns and resulted in traffic congestion. Transportation enables the movement of people and facilitates trade thereby boosting the economy, social and political relations in South Africa. There is however, a higher vehicle ownership in South Africa which makes traffic congestion one of the major problems South African cities are facing. Traffic congestion results in long journey times and a rise in road accidents which impacts negatively on economic growth. Traffic congestion also has impacts on the environment as cars then produce a large volume of carbon emissions which cause respiratory problems and global warming. Various mitigation measures have been proposed to reduce traffic congestion which among others include improving parking facilities, increasing lanes, introduction of congestion fees, park and ride facilities, high occupancy vehicle infrastructure and ridesharing. It is even so, crucial to combine the engineering factors with the economic when devising a traffic mitigation plan for a particular city. An investigation was conducted to explore high occupancy vehicles (HOV) infrastructure, and how it can be better promoted and introduced to drivers and vehicle owners. Bloemfontein which is a medium-sized city experiencing rapid growth and located in the Free State of South Africa was used as a case study. Data was collected through traffic surveys and interviews administered to drivers to. The interviews and traffic surveys were meant to determine vehicle occupancy, the nature of traffic flow as well as areas experiencing the most congestion. 150 interviews were distributed electronically and physically to drivers residing in Bloemfontein using the systematic stratified random sampling process. The intersections where the traffic surveys were conducted were selected based on the responses from the interviews which indicated where the most congestion is experienced during morning and afternoon commutes. This were intersections of roads entering the central business district (CBD) from various suburbs and locations in Bloemfontein. Traffic counts were done on weekdays in the morning and evening during peak times as reflected in the interview responses. Findings from the study showed that congestion is caused by private vehicles especially those having commuters traveling alone. Most of these commuters travel to work in the CBD resulting in arterial routes to the CBD being the most congested roads. The study also indicated that even though private vehicle owners commute alone most of them use motor cars which can carry up to 5 people. Most commuters took 6 to 14 trips per week and the peak travel times were found to be between 06:30 and 08:30 in the morning and 15:30 and 17:30 in the afternoons. Respondents showed that they are eager for introduction of HOV infrastructure with 85% of commuters indicating that they may be open to ridesharing which may significantly reduce peak hour traffic. The simulated scenarios revealed that traffic congestion decreases as vehicle occupancy increases. In turn vehicle occupancy may increase with incentives such as provision of high occupancy vehicle infrastructure which gives ridesharing commuters an opportunity to use the priority lanes. The most reduction is seen when most vehicles are full to capacity. This may be somewhat possible when HOV infrastructure is introduced in the busiest streets going to the CBD and private vehicles having more than one occupant are permitted to use HOV lanes.
Thesis (Master: Engineering: Civil Engineering)--Central University of Technology
Keywords: Congestion; Mitigation; High occupancy vehicle infrastructure; Ridesharing; African cities